Analysis of photoinduced reverse changes in bacterial reaction centers - Barabash, Y. M.; Serdenko, T. V.; Knox, P. P.; Bondarenko, O. Y. (Biophysical Bulletin, 2018)
Background: The membrane protein-pigment complexes of photosynthetic isolated reaction centers (RC) Rhodobacter Sphaeroides are macromolecular systems for studying the physical mechanisms of electron and proton transport in biological structures, the role of molecular dynamics. The experimental kinetics of cyclic electron transfer in molecular complexes has a multiexponential character with negative values of decrements. For their description, a system of balance equations is used. Objective of the work is to determine the features of the kinetics of cyclic electron transfer in the RC using two models of electron transfer and the connection of such features with space-time motions in the RC. Materials and methods: Measurement of the absorption kinetics was performed at 865 nm using a two-channel diode spectrometer. The experimental kinetics of RC absorption (the main reaction of the system) was represented by the fitting method in the form of a sum of three exponential functions. In the first model with time-variable rate constants of the balance equations, the wavelet transform method of the logarithmic derivative of the electron transfer kinetics was used. In the second model, the equation of state and three differential equations with constant coefficients were used as the algebraic sum of the rate constants. To determine the values of the rate constants in the balance equation, an optimization problem was solved. The solution of the system of balance equations by the matrix method made it possible to determine the features of the kinetics of the population of substates of the RC. Results of calculations showed that the features of the wavelet spectrum of the logarithmic derivative of the electron transfer kinetics in the first model coincided with the features of the population kinetics of substates of the RC of the second RC model. These features were in the bands 1 s, 3 s, 60 s from the moment of switching on (off) the light and depend on the photoexcitation parameters. Conclusions: The features of the kinetics of the populations of substates in the RC both at the stage of illumination and at the relaxation stage are determined by changes in the structure of the RC in the form of effects of hidden parameters of the structural self-regulation of the RC (feedback through the RC structure).